2021
DOI: 10.1017/dmp.2021.311
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy Among Patients With Epilepsy or Other Chronic Conditions

Abstract: Objectives: To investigate the opinions of different groups of people in Iran on their willingness to receive a COVID-19 vaccine. Methods: In this cross-sectional study, we surveyed a sample (based on consecutive referrals) of five groups of people in late 2020: a group of the general population from Shiraz (without a history of any chronic medical or psychiatric problems), patients with epilepsy, patients with diabetes mellitus (DM), patients with cardiac problems, and patients with psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…After screening 82 duplicates and 152 papers through titles and abstracts, we retrieved the full texts of the remaining 16 studies. Ten observational studies and two case reports studies [17] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] that met the inclusion criteria were included in this systematic review and meta-analysis ( Figure 1 ).
Figure 1 Flow diagram of study
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening 82 duplicates and 152 papers through titles and abstracts, we retrieved the full texts of the remaining 16 studies. Ten observational studies and two case reports studies [17] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] that met the inclusion criteria were included in this systematic review and meta-analysis ( Figure 1 ).
Figure 1 Flow diagram of study
…”
Section: Resultsmentioning
confidence: 99%
“…No studies provided propensity score matching analysis results. Seven studies [17] , [23] , [24] , [25] , [26] , [29] , [30] provided the information of primary outcome (vaccination status), and six studies [22] , [24] , [25] , [26] , [28] , [29] reported the secondary outcomes of vaccination willingness and unwillingness. Seven studies [17] , [23] , [24] , [25] , [26] , [27] , [30] reported the incidence of adverse effects after COVID-19 vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…The most common hesitation identified in the study was induction of seizures. Moreover, patients with epilepsy likely refuse vaccination and ask for help from professionals due to their specific conditions [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is the best hope for preventing the serious consequences of COVID-19 (i.e., severe illness and death). However, a growing number of people in the world express vaccine hesitancy [1] , [2] . In a previous study (performed in late 2020 and before the start of the vaccination campaign in Iran), we observed that about 11% of the people had vaccine hesitancy [including about 6% of patients with epilepsy (PWE)] [1] .…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing number of people in the world express vaccine hesitancy [1] , [2] . In a previous study (performed in late 2020 and before the start of the vaccination campaign in Iran), we observed that about 11% of the people had vaccine hesitancy [including about 6% of patients with epilepsy (PWE)] [1] . In another study of physicians (neurologists and psychiatrists) (conducted in September 2020 and before COVID-19 vaccines became available in Iran), about 6% of the participants expressed that they would not recommend COVID‐19 vaccines to PWE [3] .…”
Section: Introductionmentioning
confidence: 99%